Human γδ T Cell Receptor Repertoires in Peripheral Blood Remain Stable Despite Clearance of Persistent Hepatitis C Virus Infection by Direct-Acting Antiviral Drug Therapy - Ravens, Sarina; Hengst, Julia; Schlapphoff, Verena; Deterding, Katja; Dhingra, Akshay; Schultze-Florey, Christian; Koenecke, Christian; Cornberg, Markus; Wedemeyer, Heiner; Prinz, Immo (Frontiers in Immunology, 2018)
Human γδ T cells can contribute to clearance of hepatitis C virus (HCV) infection but also mediate liver inflammation. This study aimed to understand the clonal distribution of γδ T cells in peripheral blood of chronic HCV patients and following HCV clearance by interferon-free direct-acting antiviral drug therapies. To this end, γδ T cell receptor (TCR) repertoires were monitored by mRNA-based next-generation sequencing. While the percentage of Vγ9+ T cells was higher in patients with elevated liver enzymes and a few expanded Vδ3 clones could be identified in peripheral blood of 23 HCV-infected non-cirrhotic patients, overall clonality and complexity of γδ TCR repertoires were largely comparable to those of matched healthy donors. Monitoring eight chronic HCV patients before, during and up to 1 year after therapy revealed that direct-acting antiviral (DAA) drug therapies induced only minor alterations of TRG and TRD repertoires of Vγ9+ and Vγ9− cells. Together, we show that peripheral γδ TCR repertoires display a high stability (1) by chronic HCV infection in the absence of liver cirrhosis and (2) by HCV clearance in the course of DAA drug therapy.